Sleep deprivation training to reduce the negative effects of sleep loss on endurance performance: a single case study - Gattoni, C.; Girardi, M.; O`Neill, B. V.; Marcora, S. M. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Sleep deprivation (SD) is very common during ultraendurance competitions. At present, stimulants such as caffeine and naps are the main strategies used to reduce the negative effects of SD on ultraendurance performance. In this case study, the authors describe the application of a novel strategy consisting of the intermittent repetition of SD (SD training [SDT]) during the weeks preceding an ultraendurance competition.